The relationship of response time and accuracy of infecting the upper and lower target for the Epee joiner player’s - Hamid, Abedulhadi (Journal of Physical Education, 2016)
The problem of the research lies in the results of the Iraqi national fencing league that was very disappointing. The aims of the research were to identify motor response speed value and touch accuracy in the upper and lower parts of the fencer using epee as well as identifying the relationship between motor response speed and touches accuracy in youth fencers. The researchers used the descriptive method. The subjects were (10) epee fencers from youth Baghdad clubs. The data was collected and treated using proper statistical methods to come up with the results.